Analysis of Factors Affecting Minimarket Employee Performance (Case Study of Indomaret in Pemalang Regency) - Zahro Zahro (ProBisnis : Jurnal Manajemen, 2023)
Employee performance is influenced by several factors, various studies on employee performance mention several descriptions of influencing factors, including work performance, career development, motivation, commitment and so on. Research on the factors that influence employee performance is very important. An in-depth analysis of these factors can provide insights for organizational leaders to design more effective policies and strategies. This research is included in the type of causal research, because in addition to measuring the extent of the relationship between two or more variables, this research also reveals the direction of the relationship between the independent variables and the dependent variable. Data analysis is quantitative or statistical in nature with the aim of testing the hypotheses that have been set. Based on the analysis, it can be concluded that the model fit test shows a significance value of 0.000 which is smaller than 0.05, it can be suggested that the regression model is an appropriate method for measuring the effect of career development, work achievement, motivation and organizational commitment on employee performance. The results of hypothesis testing that has been done show that the effect of career development on employee performance. The results of this test show that a positive and meaningful value is obtained from career development on employee performance. The impact of work performance on employee performance, the results of the analysis that has been carried out indicate that there is a positive and significant influence between work performance and employee performance. then it can be suggested that the regression model is the right method to measure the effect of career development, work achievement, motivation and organizational commitment on employee performance.